Effectiveness of migration and human rights education applying the ARCS model among nursing students - Lee, Seung A; Lee, Sung Hee (Edelweiss Applied Science and Technology, 2025)
This study aimed to evaluate the effectiveness of the Migration and Human Rights Education Applying the ARCS model (MHREAM) program among nursing students. A quasi-experimental, one-group, pretest-posttest design was used with 23 nursing students (20 females, 3 males). The MHREAM intervention incorporated teaching and learning strategies to enhance attention, relevance, confidence, and satisfaction. The program was conducted weekly over 14 weeks, with each session lasting 75 minutes. The study measured motivation toward instructional materials and learning outcomes, including human rights awareness and sensitivity. Statistical analysis revealed significant improvements in posttest scores compared to pretest scores for the Instructional Materials Motivation Scale (IMMS), human rights awareness, and sensitivity. The results suggest that the Attention, Relevance, Confidence, Satisfaction (ARCS) model effectively enhances IMMS. Furthermore, improved human rights awareness and sensitivity through MHREAM may enable nursing students to contribute to creating healthcare environments that uphold the dignity and human rights of diverse populations, including migrants.